2007
DOI: 10.1080/10810730701672272
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Optimal Nutrition Among Women of Childbearing Age in the United States and Puerto Rico: Employing Formative Research to Lay the Foundation for National Birth Defects Prevention Campaigns

Abstract: Neural tube defects (NTDs) are serious birth defects of the brain and spine that affect approximately 3,000 pregnancies in the United States each year and affected 404 pregnancies in Puerto Rico from 1996 to 2002. Consuming the B vitamin folic acid can reduce the incidence of NTDs 50%-70%, and recent efforts to reduce NTD rates have focused on increasing the number of childbearing-aged women who take a vitamin containing folic acid every day. As the first stage of formative research in campaign planning, two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…Nine studies were conducted in the USA; 185,186,189,192,[194][195][196][197]199 one of these was colocated in Puerto Rico; 185 five were conducted in the UK, [167][168][169][170][171] three in Australia, 190,193,198 two in Canada 187,188 and one in Germany. 191 Thirteen studies evaluated adults' views concerning the taking of vitamins and minerals, 169,185,187,[189][190][191][192][193][195][196][197][198][199] five studies considered aspirin or NSAIDs, [168][169][170][171]194 two folic acid 167,185 and two dietary supplements generally. 186,188 Only four studies explored the views of participants who had either a cancer diagnosis 186,197,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies were conducted in the USA; 185,186,189,192,[194][195][196][197]199 one of these was colocated in Puerto Rico; 185 five were conducted in the UK, [167][168][169][170][171] three in Australia, 190,193,198 two in Canada 187,188 and one in Germany. 191 Thirteen studies evaluated adults' views concerning the taking of vitamins and minerals, 169,185,187,[189][190][191][192][193][195][196][197][198][199] five studies considered aspirin or NSAIDs, [168][169][170][171]194 two folic acid 167,185 and two dietary supplements generally. 186,188 Only four studies explored the views of participants who had either a cancer diagnosis 186,197,…”
Section: Resultsmentioning
confidence: 99%
“…186,188 Only four studies explored the views of participants who had either a cancer diagnosis 186,197,199 or a family history of cancer, 198 but 10 of the other included studies did focus specifically on either prevention alone 167 or the long-term management of chronic conditions, which included elements of prevention, including arthritis, 170,194 heart disease, 192,193 renal problems, 188 type 2 diabetes, 196 or a range of conditions. 168,187,191 Most studies used interviews and/or focus groups to elicit people's opinions and views on the taking of the relevant agents; 167,168,170,[185][186][187]189,190,[193][194][195][196] eight studies used structured surveys or questionnaires. 169,171,188,191,192,[197][198][199] The 15 studies identified by the initial search came from six different databases: EMBASE, 168,169,171,187 AMED, 189,191,1...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations